Development of defensive actions in small-sided and conditioned games with offensive purposes in futsal - Pizarro, D.; Práxedes, A.; Travassos, B.; Moreno, A. (Frontiers in Psychology, 2020)
Based on ecological dynamics approach, non-linear pedagogy (NLP) have emerged with the goal of promoting a holistic approach through the use of small-sided and conditioned games (SSCGs), to optimize specific tactical defensive and offensive behaviors of players. This study analyzed the indirect effects of an intervention program, based on NLP (task design based on tactical principles of attack and numerical advantage of attacking team), in decision-making (DM) and execution (Ex) in defensive technical-tactical actions in U16 futsal. Eight futsal players (U16 years) participated in 12 training sessions, spread over two phases: preintervention and intervention. The Game Performance Evaluation Tool (GPET) instrument was used to analyze the DM and Ex of 2,600 defensive actions measured during competitive matches. Results showed significant improvements in marking actions (to the player with the ball: DM, p = 0.001; Ex, p = 0.001; and to the player without the ball: DM, p = 0.039; Ex, p = 0.046), improvements in blocking actions (DM, p = 0.015), and improvements in help-coverage actions (Ex, p = 0.014). No significant differences were found in the interception and tackling actions. This study has shown evidence that the NLP approach is an appropriate theoretical framework to enhance acquisition of defensive tactical behavior in futsal. However, not all actions improved. Therefore, coaches should design representative tasks to optimally develop technical-tactical training processes based on the phases of futsal game (offensive and defensive) and considering the level of opposition.